Entrepreneurship education and its impact on students' intention to start up: A sample case study of students from two Tunisian universities. Issue 2 (July 2019) - Badri, Rim; Hachicha, Nejib
Abstract: The present paper examined the impact of entrepreneurship education on students' intention to start up a business. Using a sample of Tunisian students aged between 22 and 25 from two big Tunisian universities, namely those of Sfax and Sousse, we proposed to determine the significant factors influencing their entrepreneurial intention. Applying the ordered logistic regression, our econometric results revealed that the composite variables which are the students' internal and external socio-cultural background, their profiles in terms of theoretical and practical knowledge in new business start-up and their personal characteristics (age, gender and, above all, educational level), are the most determining variables affecting their intention to engage in business start-ups. The gender variable has no significant effect on entrepreneurial behavior. Highlights: The present paper examined the impact of entrepreneurship education on students' intention to start up a business. We proposed to determine the significant factors influencing the entrepreneurial intention. The econometric results revealed that the composite variables which are the students' internal and external socio-cultural background, their profiles (age, gender and, above all, educational level), are the most determining variables affecting their intention to engage in business start-ups. The gender variable has no significant effect on entrepreneurial behavior.